Outcome of Flexible and Semirigid Ureteroscopy in the Management of Proximal Ureteral Stones Using Laser Lithotripsy (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Proximal ureteric stone often poses therapeutic challenges to urological surgeons. Currently, management of ureteric stone is highly successful with Ho:YAG laser lithotripsy using flexible and semi-rigid ureteroscope.Objectives: The objective of the study to evaluate comparative clinical efficacy and safety of flexible and semi-rigid ureteroscopy combined with Ho: YAG laser lithotripsy for treating proximal ureteral stone in real-world settings.Methods: This study was conducted as a clinical trial. A total of 82 patients were included in the study through purposive sampling and divided into two comparison groups: Group A (Flexible ureteroscopy with laser lithotripsy) and group B (Semi-rigid ureteroscopy using laser lithotripsy). Follow-up visits were conducted at 1 and 3 month post-operatively to track the stone clearance rate and post-operative complications (hematuria, migration of stone, mucosal disruption, and ureteral stricture). Data analysis was conducted using SPSS version 21, and the chi-square test was used to compare percentages of different outcome variables. A p-value of less than 0.05 was considered statistically significant.Results: Among 82 prospective cases, 22 patients were lost to follow-up, leaving 60 patients for final analysis; 75% of patients were males and 25% of them were females, mean of age were 36.21±12.58 and 34.94±10.23 years, respectively ranging from 19 to 65 years, with laterality of 57.1% and 53.1% (Group A and Group B respectively) of patients were right but of 42.9% and 46.9% respectively were left. The mean operative time were 65.0±9.33 minutes and 55.25±11.46 minutes, respectively and mean duration of hospital stay (in both groups) was 51 hours. The mean ureteral stone diameter was 10.57 mm and 10.16 mm respectively. The clearance rate 89.3% and 65.6%.Conclusion: Flexible ureteroscopy combined with laser lithotripsy is a highly effective option for treating proximal ureteral stones than semirigid ureteroscopy with laser lithotripsy regarding superior stone-free rates.J Com Med Col Teachers’ Asso July 2025; 29(2): 127-132